Turismo pedagógico: o aproveitamento turístico da área de proteção ambiental Baleia Sahy como instrumento de educação ambiental. - ALVES, João Vitor Tavares; SANTOS, Priscilla Costa dos; MARQUES, Tawanny Mablis Lima (188, 2023)
A cidade de São Sebastião é constituída por uma diversidade de atrativos turísticos, variando de atrações no mar, na Mata Atlântica, além do aspecto histórico. Esses elementos interpretados como matéria-prima do turismo podem ser utilizados como instrumento de ensino e aprendizagem. Essa diversidade tem um conteúdo que permite ao destino ser considerado uma espécie de laboratório a céu aberto. O trabalho de pesquisa adotou a Área de Proteção Ambiental localizada entre as Praias da Baleia e Barra do Sahy para propor formas de consumir o espaço, com um olhar racional e sustentável. A forma pertinente de consumir o espaço, ou seja, o uso público, é a caracterização para a prática do Turismo Pedagógico. Para isso é preciso elaborar atividades para visitação. O trabalho de pesquisa tem como intenção colocar em prática o conceito de Turismo Pedagógico na APA Baleia Sahy, localizada na costa sul de São Sebastião para trabalhar a questão da sensibilização ambiental, fomentar um novo segmento e contribuir para o fortalecimento da economia vinda do turismo.

The city of São Sebastião is made up of a variety of tourist attractions, ranging from the sea to the Atlantic Forest, as well as the historical aspect. These elements, interpreted as the raw material for tourism, can be used as a teaching and learning tool. This diversity has a content that allows the destination to be considered a kind of open-air laboratory. The research project used the Area of Environmental Protection located between the Baleia and Barra do Sahy beaches to propose ways of consuming the space, with a rational and sustainable approach. The pertinent way of consuming the space, i.e. public use, is the characterization for the practice of Pedagogical Tourism. To do this, it is necessary to design activities for visitors. The aim of this research is to put the concept of Pedagogical Tourism into practice at the Area of Environmental Protection Baleia Sahy, located on the south coast of São Sebastião, in order to raise environmental awareness, promote a new segment and help strengthen the tourism economy. The visits to the Baleia Sahy Environmental Protection Area were an important opportunity for the students on the Travel Agency course. The research proposal respects the phases adopted by the Coastal Conservation Institute for Planning, Implementing and Monitoring Public Use of the Environmental Protection Area. At the moment, it is up to the implementation to turn the site into an attraction with itineraries of educational interest.
Pedagogical tourism: the tourist use of the Baleia Sahy area of environmental protection as an instrument of environmental education.
Keywords: Turismo litorâneo; Proteção ambiental; Turismo ecológico; Educação ambiental; Turismo, Hospitalidade e Lazer